2013
DOI: 10.1186/2191-219x-3-44
|View full text |Cite
|
Sign up to set email alerts
|

SERT-to-DAT ratios in early Parkinson’s disease do not correlate with the development of dyskinesias

Abstract: BackgroundAlthough the treatment of Parkinson’s disease (PD) is very effective, in the course of the disease, 40% to 60% of patients develop dyskinesias. The pathophysiology of dyskinesias is still unclear. Results of preclinical research suggest that uptake and uncontrolled release of dopamine by serotonergic neurons is an important factor. Based on this model, we hypothesized that dyskinesias will develop predominantly in PD patients with a relatively preserved serotonergic system.MethodsBetween 1995 and 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…Finally, positron emission tomography imaging of patients who developed graft‐induced dyskinesias suggest that the role of 5‐HT innervation in LID is dependent on the extent of residual dopaminergic function . However, recent single‐photon emission computed tomography (SPECT) study of early‐stage PD patients found that baseline SERT/DAT ratios did not correlate with the development of LID later in the disease . Our data confirm this observation in advanced PD, because no difference was observed in striatal SERT/DAT ratio between patients with and without LID in this study (Supplemental Data Table 3).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Finally, positron emission tomography imaging of patients who developed graft‐induced dyskinesias suggest that the role of 5‐HT innervation in LID is dependent on the extent of residual dopaminergic function . However, recent single‐photon emission computed tomography (SPECT) study of early‐stage PD patients found that baseline SERT/DAT ratios did not correlate with the development of LID later in the disease . Our data confirm this observation in advanced PD, because no difference was observed in striatal SERT/DAT ratio between patients with and without LID in this study (Supplemental Data Table 3).…”
Section: Discussionsupporting
confidence: 79%
“…However, recent single-photon emission computed tomography (SPECT) study of early-stage PD patients found that baseline SERT/DAT ratios did not correlate with the development of LID later in the disease. 39 Our data confirm this observation in advanced PD, because no difference was observed in striatal SERT/DAT ratio between patients with and without LID in this study (Supplemental Data Table 3).…”
Section: H E S H I R E E T a Lsupporting
confidence: 88%
“…The authors showed that imbalanced ratios do not predict the development of LIDs in early stages of the disease, but hypothesized that imbalance ratios may occur at later stages of PD. 30 Our study suggests that the putaminal SERT-to-DAT terminals ratio is a good index to quantify in vivo the serotonergic over dopaminergic terminals' activity. Using PET and SPECT imaging, we have shown that the presence of LIDs is related to an imbalanced serotonergic-over-dopaminergic terminals density ratio in the putamen.…”
mentioning
confidence: 99%
“…However, a study using post-mortem brains of PD patients measured a significant decrease of SERT levels only in the caudate nucleus and not in the putamen, while no difference in SERT levels was observed between PD patients with or without LID (Kish et al, 2008). Moreover, SERT-to-DAT ratios in early-stage and untreated parkinsonian patients were shown not to correlate with the future development of LID (Suwijn et al, 2013).…”
Section: Effects Of a Chronic Treatment With L-dopa And Mpep On Basalmentioning
confidence: 86%